2014
DOI: 10.1111/jeb.12316
|View full text |Cite
|
Sign up to set email alerts
|

Rapid increase in dispersal during range expansion in the invasive ladybird Harmonia axyridis

Abstract: The evolutionary trajectories associated with demographic, genetic and spatial disequilibrium have become an issue of growing interest in population biology. Invasive species provide unique opportunities to explore the impact of recent range expansion on life-history traits, making it possible to test for a spatial arrangement of dispersal abilities along the expanding range, in particular. We carried out controlled experiments in laboratory conditions to test the hypothesis of an increase in dispersal capacit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
98
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(105 citation statements)
references
References 77 publications
(103 reference statements)
7
98
0
Order By: Relevance
“…It is also possible that non-neutral genetic variation was introgressed into the native gene pool [7,59,60] which may alter local adaptation within an already small and threatened wild population and ultimately fail to contain its demographic decline [12,61]. Alternatively, this genetic admixture may have potential (and unnoticed) beneficial effects for the fitness of wild populations as often reported in non-native species for which multiple introductions of different lineages strongly contribute to their success in the invaded range [4][5][6]62,63]. The differences observed in life traits also suggested that supplementation programmes should carefully consider potential mechanisms leading to deviations from the life traits observed in the wild stocked populations.…”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that non-neutral genetic variation was introgressed into the native gene pool [7,59,60] which may alter local adaptation within an already small and threatened wild population and ultimately fail to contain its demographic decline [12,61]. Alternatively, this genetic admixture may have potential (and unnoticed) beneficial effects for the fitness of wild populations as often reported in non-native species for which multiple introductions of different lineages strongly contribute to their success in the invaded range [4][5][6]62,63]. The differences observed in life traits also suggested that supplementation programmes should carefully consider potential mechanisms leading to deviations from the life traits observed in the wild stocked populations.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the effects of range expansions on several evolutionary processes have been empirically and theoretically studied. These processes include the evolution of dispersal (Lindström et al 2013;Lombaert et al 2014), life-history traits (Burton et al 2010), or cooperation (Datta et al 2013). The growing appreciation of the consequences of dynamic range margins on the ecology , population genetics (e.g., Excoffier et al 2009), and behavior (Lindström et al 2013) of species has changed our views about several evolutionary processes, such as the evolution of dispersal (Shine et al 2011) and the spatial structuring of biodiversity (Waters et al 2013) or genetic diversity ).…”
Section: Introductionmentioning
confidence: 99%
“…Also, it has a strong dispersal capacity. During its invasion of Europe it has spread at rates estimated between 100 and 200 km year -1 (Brown et al 2011) and Lombaert et al (2014) showed that several traits related to dispersal have evolved in less than a decade. Further, H. axyridis populations may have profited until now from lack of natural enemies (Roy et al 2011) as it invaded without or with few of its native natural enemies, and/or the natural enemies in the invaded area are not (yet) effectively attacking the exotic species (Haelewaters et al 2017;.…”
Section: Discussionmentioning
confidence: 99%